Stabilitas madu herbal dengan penambahan emulsifier dan antioksidan menggunakan metode spontan - Nur Ahmad Habibi; Nur Heni Sri Palupi; Azis Boing Sitanggang (Jurnal Litbang Industri, 2020)
Herbal honey with blackseed oil and olive oil is susceptible to change in stability during the storage period, such as separation and oxidation. The aim of this study was to observe the effect of emulsifier and antioxidant to stability of herbal honey. This study used a completely randomized factorial design with two repetitions. The first factor was concentration antioxidant tocopherol (0; 0,005; 0,01%) and the second factor was concentration of emulsifier Tween 80 (0; 0,001; 0,002%) so there were 9 combinations. Herbal honey was made using the spontaneous method. The study observed particle size distribution, stability against separation, and predict shelf life. Based on observation, the largest particle size distribution was in the herbal honey T1TW1 group  with size 1004.70 ± 5.80 nm. The smallest particle distribution was in the T3TW3 group with size 117.10 ± 1.56 nm. Based on the stability, T3TW3 group was able to keep the rate of emulsion separation that occurs compared to other groups. Based on ASLT test, herbal honey with antioxidan and emulsifier had shelf life 241 days and without 140 days. Conclusion this study is antioxidant tocopherol and Tween 80 emulsifier can improve the stability of herbal honey significant.